Characterization of circRNA-Associated-ceRNA Networks Involved in the Pathogenesis of Postoperative Cognitive Dysfunction in Aging Mice - Zhang, Meng-Xue; Lin, Jing-Run; Yang, Shu-Ting; Zou, Jun; Xue, Yao; Feng, Chen-Zhuo; Cao, Lin (Frontiers in Aging Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is a clinical entity associated with declined cognitive function following surgery. It occurs more frequently in elderly patients. Recent studies have shown that circRNA-associated-ceRNA networks, constructed based on interactions between circRNA-miRNA and miRNA-mRNA, provide key insight into the molecular mechanisms underlying the pathogenesis of several neurological diseases. However, the mechanism of POCD remains undetermined. In this study, laparotomies were performed under isoflurane anesthesia on young (2-month-old) and aging (17-month-old) male C57BL/6 mice. The results showed that the aging mice were more likely than the young mice to develop POCD. Subsequently, differentially expressed circRNAs, miRNAs, and mRNAs were characterized by RNA sequencing the hippocampi of young and aging mice under control and surgery conditions. Six circRNAs, 6 miRNAs, and 203 mRNAs were identified to construct the circRNA-associated-ceRNA network for the control condition, while 13 circRNAs, 8 miRNAs, and 189 mRNAs were used for the circRNA-associated-ceRNA network for the surgery condition. Further Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of these two networks revealed that the circRNA-associated-ceRNA networks are involved in POCD pathogenesis though modulating the Wnt and VEGF signaling pathways, as well as neural processes associated with long-term synaptic depression and synaptic transmission. In particular, the mmu-miR-298-5P regulatory pathway identified in this study’s mouse model suggests that mm9_circ_009789- and mm9_circ_004229-associated-ceRNA networks as closely related to the occurrence of POCD through regulating PKC signaling pathway, neural cell apoptosis and glycolipid metabolism pathway. These findings provide possible insight into the role of the circRNA-associated-ceRNA networks, helping to unravel the complexity of the molecular pathogenesis of POCD.